Estimation of Water Carrying Capacity for Floating Net Cage Cultivation Activities in Pekalongan Coastal Waters - Tri Yusufi Mardiana; Heri Ariadi; Linayati Linayati; Wijianto Wijianto; Ashari Fahrurrozi; Maghfiroh Maghfiroh (Jurnal Perikanan Universitas Gadjah Mada, 2023)
Floating cage fish farming is an aquaculture activity that is mostly carried out on the coast of Pekalongan. The purpose of this study was to estimate the carrying capacity of Pekalongan coastal waters as a floating net cage aquaculture activity zone. The research method used is descriptive qualitative and quantitative descriptive by calculating the indicators of Trophic Status Index (TSI), phosphorus, feed conversion ratio, and the carrying capacity level of the waters. The results showed that chlorophyll-a values ranged from 6.44-8.24 ê’g/L, total phosphorus 12.44-14.80 ê’g/L, feed conversion ratio 1.10-1.25, TSI (Trophic Status Index) values 48.2-54.6, harvested biomass 120-157 kg/ floating net cages (KJA). The carrying capacity of the waters for KJA cultivation is 145.43 tons of fish/year, and the number of existing KJA for cultivation is 110 KJA. The conclusion from the results of this study is that the carrying capacity on Pekalongan coastal waters when used as a floating net cage aquaculture activity zone is estimated to be able to accommodate approximately 145.43 tons of fish/year or the equivalent of 121 KJA. Currently, there are 110 KJA plots in the Jeruksari coastal waters, which means that the maximum carrying capacity of the waters that can be used for KJA cultivation is 11 KJA.